Tumoral Calcinosis: Case Report and Review - Vaghasiya, Piyush; Shetty, Lathika; Shetty, Molahalli Shantharam; Kumar, Muthur Ajith (Journal of Health and Allied Sciences NU, 2020)
Tumoral calcinosis (TC) is an uncommon disorder characterized by the deposition of calcium phosphate in periarticular tissues. TC has been a controversial clinico-pathological entity first described in 1943. The calcium deposits are usually present in the large joints such as the hips and shoulders. Patients often present with localized swelling and reduced mobility around the involved joints which interfere with activities of daily living. A 12-year-old boy presented at our clinic with a painful swelling around his left elbow joint with 6-month duration over which the swellings progressively increased. Radiological imaging identified a soft tissue calcified mass present around both elbow joints. Excision and biopsy of the left elbow demonstrated a tumor consisting of myxoid material with multiple areas of calcification with a well-defined capsule. Microscopy confirmed typical features of TC. We present our case report due to unusual clinical presentation noted in this case.
Keywords: tumoral calcinosis; calcification; calcium deposition; tumor; KLOTHO; phosphate binders